ANALISIS BORAKS DENGAN EKSTRAK BUNGA TELANG PADA KERUPUK PULI - Ni Putu Eka Trisdayanti (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Borax is a chemical that is prohibited from being used in food but is often misused by producers. One of the foods that is often added to borax is Puli crackers with the aim of increasing the crispness and longevity. However, the addition of borax in these Puli crackers can have a toxic effect on consumers. Therefore, consumers must be smart in distinguishing between foods that contain borax or not. To be able to distinguish them, an easy method is needed using natural ingredients, so this study aims to detect borax in Puli crackers using telang flower extract. The method used in this research is the experimental extraction of the telang flower extract with the maceration method, and the sample testing using the extract. The results showed that of the 8 samples of Puli crackers tested, 3 samples were positive for borax which was indicated by a blue to green color change.